Supporting and hindering environments for participation of adolescents diagnosed with autism spectrum disorder: A scoping review - Krieger, Beate; Piškur, Barbara; Schulze, Christina; Jakobs, Uta; Beurskens, Anna; Moser, Albine (PLOS ONE, 2018)
The influence of a person’s environment and its modifying potential on participation is well recognized for most childhood disabilities, but scarcely studied for adolescents with autism spectrum disorder (ASD). A scoping review was conducted, the aim of which was to map the existing literature about supporting and hindering environments for the participation of adolescents with ASD. Sources of scientific evidence were searched for in four databases. Inclusion criteria were the perspectives of adolescents between 12 and 21, families, peers, or significant others; ecologic validity; and a clear connection between environment and participation. The publication dates ranged from 2001 to 2014 and partly up to 2018. The International Classification of Functioning, Disability and Health (ICF) served as the guiding framework for inclusion/exclusion during the selection process. Thematic analysis was performed by five independent reviewers. Results were additionally validated by stakeholders. This scoping review identified 5528 articles, and finally included 31 studies. Two main themes were found: “providing security” indicates how the environment, and specifically the parental, physical, and informational environments, have a securing or intimidating effect. The second theme, “helping to connect”, indicates which environments support or hinder social relationships or social activities, and hence participation. An additional third main theme, “tension in participation”, relates to ambiguities that seem essential to understand participation or isolation of adolescents with ASD. Results show that participation is a value-laden concept. This research widens the field of dealing with adolescents with ASD, as it directs attention towards the responsibility of the environment regarding participation.